Efficiency of Defoliation on Low Salt Fields - Uljaboev Alijon Abdullajonovich; Kozimjonova Munisakhon Nodirjon (Peerian Journals Publishing, 2022)
A high effect was established in comparison with the liquid HMD defoliant, control, with the use of FanDEF defoliant at a rate of 5.0-6.0 l/ha, UzDEF 6.0 l/ha on moderately saline, as well as at a rate of 7.0 l/ha UzDEF and FanDEF on non-saline and slightly saline soils with an opening of 45-50%, boxes of the Sultan variety in the conditions of the Andijan region. In the conditions of slightly saline soils of the Andijan region, during the opening of 45-50% of the bolls of the Sultan cotton variety, the use of defoliants UzDEF and FanDEF with a norm of 7.0 l / ha, leaf fall was 90.0-86.9%, opening of the bolls 91.5-89 ,1%, the yield of raw cotton is on average 30.5 q/ha
Keywords: Meadow-saz soils; seeds; cotton; budding